The Technological Foundations of Education: A philosophical, Theorical and Practical Analysis in The Digital Era - Jasman, Yulia Oktafia; Ilmi, Darul (STIT Ahlussunnah Bukittinggi, 2025)
The rapid development of information and communication technology (ICT) has triggered fundamental changes in the paradigm of modern education. This article aims to analyze the technological foundations of education from philosophical, theoretical and practical perspective within the context of 21st-century learning. This study employs a library research method using a descriptive qualitative approach, collecting and synthesizing recent academic sources such as journal articles, scholarly books and research report related to the integration of technology in education. The findings indicate that understanding the philosophical foundations including ontological, epistemological and axiological dimensions essential for guiding ethical and meaningful technological use. Theoretically, the integration of learning theories and systems theories strengthens the conceptual framework for implementing educational technology. Practically, technology enhances the effectiveness, interactivity and accessibility of learning. However, the teacher’s role remains central in directing and humanizing digital learning processes. The implications of the study highlight the necessity of strengthening digital literacy, technology-based instructional design, and ethical ICT use among educators and institution to ensure that digital transformation remains aligned with humanistic values and national educational goals.